Spiritualitas dalam Pendidikan : Mengembangkan Iman melalui Kurikulum Pendidikan Agama Kristen - Anggi Fatma Triyani; Timotius Ferry Setiawan; Andinna Salsabela (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article examines how Christian religious education curriculum can be a means to develop students' faith. This study uses a phenomenological approach to explore students' and teachers' experiences in the learning process. Findings suggest that spirituality-based approaches, such as prayer, meditation, and biblical reflection, are effective in fostering deep faith. This article recommends a curriculum model that is more integrated with spiritual practices.